Pedagogic conditions of health saving functioning organization of comprehensive educational estableshment's headmaster - O.V. Gres (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: substantiation of pedagogical conditions of health saving functioning organization of comprehensive educational establishment's headmaster. Material: publications on topic of the research. 40 literature sources have been analyzed. Results: it has been found that pedagogic conditions of effective health saving functioning of comprehensive educational establishment headmaster are: influence of interconnection of district educational administration's teaching-methodic departments; activation of headmaster's personality; understanding of values by headmaster and his acquiring of health related knowledge and knowledge about health saving in process of education; realization of self-education by headmaster; renewal and acquiring of new knowledge and experience, which would ensure personal-professional growth of headmaster and facilitate increase of quality of pupils' education and teaching. Conclusions: self-education provides wide opportunities for improvement of administrative, communicative and reflexive qualities and skills as well as gives proper tools for independent and creative solution of health saving tasks in favor of pedagogic process's subjects.